The scientific contributions of scholars kurdish country to islamic civilization through the book (mukhtasar fi akhbar al-bashir) by abu al-fidaa in the (sixth century ah / twelfth century ad) - Sadeeq, Ahmed; Omar, Ardalan (Humanities Journal of University of Zakho, 2023)
The researcher attempted to shed light on the Kurdistan figures that have great contributions in Islamic civilization, which are cited in the book entitled ''Mukhtasar fi Akhbar Al-Bashir'' written by Abi- fida Ayoobi in ''6th hijri/12th gregorian'' century, Among these scholars is the historian Mohammed bin Abdul Malik Al-Hamathani, the poet Yahia bin Salama Al-Haskafi, the jurisprudent Omer bin Ikrima Al-Jazari, the Worshipper Auday bin Musafir Al-Hakari, Mowaffag Al-deen Al-Arbeeli and Ibin Mustawfi Al-Arbeeli, in addition to other scholars who devoted their lives to serve the islamic civilization, These scholars are the pride and admired by most people due to their significant contributions.